"… langt der oppe mot nord." Bilder av nord i nordnorsk lyrikk – fra Elias Blix til Morten Wintervold. - Wærp, Henning Howlid (Nordlit, 2015)
Published version. Source at http://dx.doi.org/10.7557/13.3427 . The article gives a survey of northern Norwegian poetry from the end of the eighteenth century until the present, focusing on how the north is depicted. Another line in the article follows the shaping of a specific northern Norwegian identity from the launching of the name “Nord-Norge” (North Norway) in 1884. The argument is that the feeling of marginalisation is no longer evident, probably because a new circumpolar identity has emerged, an international orientation replacing the former comparisons and competition with the capital in the south.